Peritumoral edema in meningiomas: a review of influencing factors, mechanisms, and management - Zhang, Gaocai; Wu, Erman; Li, Yandong; Zhang, Yongtao; Lian, Minghao; Geng, Dangmurenjiafu; Zhu, Guohua (Frontiers in Oncology, 2026)
Peritumoral brain edema is an accompanying symptom of meningiomas, and its severity impacts patient symptoms and prognosis. Meningioma-related peritumoral brain edema can result in severe symptoms such as neurological disturbance and brain herniation. Traditionally, the main treatment options for peritumoral brain edema in the perioperative period have been osmotherapy and corticosteroids, but the side effects and limited effectiveness cannot be ignored. This review summarizes the known influencing factors and mechanisms that contribute to meningioma-related brain edema, discusses the limitations of existing edema treatments, and outlines future edema treatments. More research on meningioma-related peritumoral brain edema is needed to improve patient outcomes and enhance treatment efficacy.